Dialogic Teaching during Cooperative Inquiry-Based Science: A Case Study of a Year 6 Classroom - Robyn M. Gillies (MDPI AG, 2020)
Teachers play a critical role in promoting dialogic interaction in their students. The purpose of this case study was to investigate how one very effective teacher taught two, cooperative, inquiry-based science units to her Year 6 class. In particular, the case study focused on how she used different discourses to capture students' curiosity in the inquiry-based tasks, provided hands-on activities to enable them to test out their hypotheses and develop explanations for what they found in order to help them become more scientifically literate and have a broader understanding of the role of science in the world in which they live. The results showed that the students engaged constructively with their peers on the inquiry group tasks; they used the correct scientific language to discuss phenomena, make claims, and compared findings. Furthermore, they became more adept at expressing their opinions and providing explanations and justifications for the 'scientific' positions they had adopted across the six inquiry-based science lessons; core cognitive practices that support learning. This case study highlights the importance of utilizing both authoritative and dialogic discourse to challenge and scaffold students' thinking to support enhanced understandings and reasoned argumentation during inquiry-based science. This case study fills a gap in the literature on how teachers can utilize different communicative approaches during inquiry-based science units to promote student engagement and learning.